Brand dan Public Relation: Sebuah Kajian Konseptual dalam Konteks Indonesia - Dewi Warda Wibowo; Avizatuz Zahro; Pratiwi Yuni Rahayu; Miftahul Huda (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
This research aims to analyze the conceptual relationship between brands and public relations (PR) in the context of business and socio-cultural dynamics in Indonesia. Through a literature study method with a qualitative approach, this research explores the role of PR in building brand identity, managing reputation, and facing challenges in the digital era. The study focuses on three main aspects: (1) the development of the brand concept in Indonesia which is not only a visual identity, but also a representation of values ​​and emotional relationships with consumers; (2) definition and function of PR as a strategic communication tool to create a positive image; and (3) integration of brand and PR in a communication strategy that is adaptive to local characteristics. Initial findings show that brand-PR synergy in Indonesia requires a participatory approach, message consistency, and the use of digital media, emphasizing cultural values ​​such as family and religiosity.